Rheological behavior of molasses for application in industry - Santos Bofo, Daniele Cristina dos [UNESP]; Ferreira Cabral, Renato Alexandre [UNESP]; Andrietta, Silvio Roberto; Telis-Romero, Javier [UNESP] (Wiley-Blackwell, 2016)
Molasses is a by-product from the raw sugarcane industry with vast applications in the production of ethanol biofuel. A good knowledge of the rheological properties of this raw material is of crucial importance when designing and optimizing unit operations involved in processing it. The present work thus aims to study the rheological behavior of molasses at solid concentrations ranging from 20 to 70 (o)Brix and temperatures between 21 and 98 degrees C using a concentric-cylinder rheometer. Experimental results showed Newtonian behavior in concentrations of 20 and 40 (o)Brix and pseudo-plastic behavior in concentrations of 50 and 70 (o)Brix. For these results, the Power Law models presented the best fitting results. In addition, the dependence of the flow behavior index and the flow consistency index of the Power Law model on temperature and solid concentration was also successfully modeled through a polynomial model and an Arrhenius-type equation, respectively. (c) 2016 American Institute of Chemical Engineers Environ Prog, 35: 1545-1552, 2016
Keywords: ethanol industry; modeling; Newtonian behavior; pseudo-plastic behavior; unit operations